MAKTABGACHA TA‘LIMDA MUAMMOLI VAZIYATLARDAN FOYDALANISHNING PEDAGOGIK ASPEKTLARI - Ergasheva Sarvinoz Ulug'bek qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article outlines methodologies for making good use of problematic situations in education and their use as a methodological weapon in the pedagogy of young educators today, which is viewed as one of the most pressing issues in the preschool education system today. In addition, this scientific paper outlines general and private aspects of problematic situations in about 10 preschool organizations studied. The research process reflected the most common problem situations in educators in the educational organization until the invented school and their status in the form of charts and charts.